POEMS Syndrome. A Case Presentation - Iris González Morales (Medisur, 2011)
The case of an 85 years old patient admitted in the General University Hospital "Dr. Gustavo Aldereguía Lima" of Cienfuegos is presented. The patient would undergo a chronic anemia study with endocrine manifestations compatible with hypothyroidism, organomegaly, peripheral polyneuropathy and skin alterations. These deductions were ratified with the results of the tests and the patient was diagnosed with Poems syndrome (multisystem disorder presenting changes in several organs). An analysis on the clinical findings is presented as well as comments on this case and a brief literary review on the topic.